Hubungan Status Gizi Ibu Saat Hamil dengan Kejadian Stunting di Wilayah Kerja Unit Pelaksana Teknis Puskesmas Kintamani VI Tahun 2022 - Putu Cindy Anitya; Asep Arifin Senjaya; Ni Ketut Somoyani (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2023)
The main nutritional problems for toddlers were stunting and malnutrition. Stunting or short was one of the malnutrition which was characterized by a height that did not match the development of the child's age or height according to and causes disturbances in physical development which caused a decrease in cognitive, motoric abilities and decreased work performance. Children with stunting had an IQ (Intelligence Quotient) lower than normal children. The state of SEZ and maternal anemia during pregnancy would affect the growth and development of toddlers. The purpose of this study was to determine the relationship between maternal nutritional status during pregnancy and the incidence of stunting in the working area of UPT.Puskesmas Kintamani VI in 2022. This type of research was observational with a cross sectional design. The sample size was 29 people, from the cohort register. Bivariate analysis using Fisher's exact test. The frequency of pregnant women who have a LILAâ‰¥ 23.5 cm was 70.3, pregnant women with Hb 11 g/dl were 89.7%, toddlers experiencing stunting in 2022 were 20.7%. There was a relationship between the nutritional status of the mother during pregnancy and the incidence of stunting in the UPT working area. Puskesmas Kintamani VI in 2022 with a p value of 0.018. To the Puskesmas to improve health promotion, especially regarding nutrition during pregnancy. Â